ANTECEDENTS AFFECTING GOOD ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND EMPLOYEE PERFORMANCE EFFICIENCY IN AUTOMOTIVEPARTS INDUSTRIES - Samantreeporn, Saowanee (Journal of Buddhist Anthropology, 2020)
The main objective of this study was to antecedents affecting good organizational citizenship behavior and employee performance efficiency in automotive parts industries. And to study the indirect effect of the mediating variable by good organizational citizenship behavior. The population of the study was operational staff in various automotive parts industries in Rayong and Chonburi provinces amount 11,035. The sample size was determined by the known formula of the population size of Taro Yamane, there are a total of 314 samples. This study used probability sampling with stratified sampling and nonprobability sampling with purposive sampling. The study instrument was a set of questionnaires and analyzed data using descriptive statistics including frequency, percentage, mean and standard deviation and inferential statistics by structural equation modeling. An a result of the data analysis, it was found that there was consistency between the structural equation model and the empirical data; the derived values were; Chi-square = 222.698, p-value = 0.000, Chi-square/df = 1.754, GFI = 0.934, AGFI = 0.902, NFI = 0.906, CFI = 0.956 and RMSEA= 0.049. The hypothesis testing confirmed the fact that vertical leadership, interpersonal relationship, organizational climate and perceived organizational support had direct effect on employee performance efficiency in automotive parts industries. The relationship had a statistical significance of 0.05, and the prediction power was found to be 97 percent, whereas the indirect effect on the employee performance efficiency of the organizational citizenship behavior was found to have statistical significance at the .05 level and the predictive power was 52 percent.